Effect of thrombus size on recanalization by bridging intravenous thrombolysis. (21st July 2014) - Behrens, L.; Möhlenbruch, M.; Stampfl, S.; Ringleb, P. A.; Hametner, C.; Kellert, L.; Pham, M.; Herweh, C.; Bendszus, M.; Rohde, S.
<x xml:space="preserve">Abstract</x> Background and purpose Thrombus length has been reported as an important predictor of successful recanalization by intravenous thrombolysis but its influence on bridging thrombolysis has not been investigated yet. The effect of thrombus length on recanalization rates evaluated by catheter angiography early after intravenous bridging thrombolysis was analyzed. Methods Ninety‐six consecutive patients with acute cerebral artery occlusion were included. Occlusion site and thrombus length on initial computed tomography angiography or magnetic resonance angiography were related to recanalization after intravenous bridging thrombolysis on the initial series of catheter angiography. Results Eleven of 96 patients (11.5%) showed successful recanalization (TICI 2a, 2b or 3) after intravenous bridging thrombolysis. Mean thrombus length in these patients was 10.8 mm as opposed to 15.6 mm in patients without successful recanalization. No thrombus longer than 16 mm showed complete recanalization. Binary logistic regression demonstrated a significant influence of thrombus length on probability of recanalization (odds ratio 0.78, 95% confidence interval 0.65–0.95; P = 0.014). Conclusions Thrombus length is a significant predictor of recanalization rates after bridging thrombolysis. Overall recanalization rate within the time frame until interventional treatment is started was 11.5% after bridging thrombolysis.